A New Perspective on the Status of the Intestinal Parasitic Infections in the Rural Areas of Fars Province South of Iran from 2015-2016 - Mojtaba NOWROZI; Gholam Reza MOWLAVI; Mostafa ALISHAVANDI; Gholamreza HATAM (Tehran University of Medical Sciences, 2019)
Background: Parasitoses are among the most important problems of most countries especially developing countries. We aimed to detect the situation of intestinal parasitic infections in the Farashband district in Fars Province South of Iran and identify influential factors in the escalation of parasitic diseases and to reduce them. Methods: Overall, 1009 participants from the age of 6 months to 90 years were selected from 3 cities and 15 villages of Farashband district, Fars Province South of Iran from 2015 to 2016. Parasitological methods such as the direct assay method, formalin-ether concentration method, and zinc sulfate flotation were used for diagnosis of worm eggs, cysts, and protozoa trophozoite. Susceptible and protozoan positive samples were stained using the Trichrome staining method. The modified acid-fast staining procedure was conducted for diarrheal samples and the results were used for diagnosis of coccidia. Results: Overall, 313 subjects were infected with at least one intestinal parasite (pathogenic and nonpathogenic). Helminthes infection and protozoan infection were observed in 9 (0.9%) and 304 (30.13%) participants, respectively. Fecal samples of 34 patients with diarrheal feces were used to prepare smears for further examinations using the Ziehl-Neelsen staining method. Examinations showed no infection with coccidia. Conclusion: Helminthes infection has decreased drastically but protozoan infection is still considered a health issue in this region. It is possible to reduce parasitic infections through proper measures such as increasing public awareness and education the public, especially children on health problems with education courses.